Methods of Determining Forces and Equipment in the Designing of Fire and Rescue Services - Bakhtiyarovich, Akhmedov Allayar; Ergashevich, Kurbanbaev Shukhrat (International Journal on Orange Technologies, 2023)
This article explains the algorithm of determining the forces and equipment necessary for fire and rescue services in the designing of fire and rescue garrison services organized to ensure the fire safety of cities, regions and settlements.